ANALISIS KAUSALITAS STRATEGI DIVERSIFIKASI DAN KINERJA PERUSAHAAN - Novita; Mulyani Mulyani (Jurnal Akuntansi, 2020)
Firm diversification is the level of development a firm undertakes both through the number of firms it manages and the level of its business segments (at least two business segments). Based on agency theory, companies with multi-segments are suspected of placing too large investment in their line of business with low investment opportunities. Meanwhile, according to market power theory, only conglomerate companies are able to diversify well. Previous research stated that even if conglomerate companies diversify, it may lead to firm performance’s loss. This study aims to determine the influence of diversification level, investment opportunities, firm size, leverage, and number of segments on the firm performance of manufacturing companies. The conclusion of this study shows that there is insufficient evidence that diversification level and number of segments has a negative influence on company performance. Also, there is insufficient evidence that leverage has a positive influence on company performance. Meanwhile, there is sufficient evidence that investment opportunities and firm size have a positive influence on firm performance. Keywords: Firm Performance, Diversification Level, Investment Opportunity, Company Size, Leverage, Number of Segments. References: Amyulianthy, R., & Sari, N. (2013). Pengaruh diversifikasi terhadap kinerja perusahaan. Binus Business Review, 4(1), 215–230. Aprilia, W., Rodhiyah, & Widiartanto. (2015). Analisis pengaruh kinerja keuangan perusahaan terhadap return saham perusahaan sektor jasa transportasi yang terdaftar di bursa efek Indonesia. Winindya Aprilia Jurusan Administrasi Bisnis , Universitas Diponegoro Semarang Jl . Prof . H Sudharto , SH . Tem. 1(1), 155. Berger, P. G., & Ofek, E. (1995). Diversification’s effect on firm value. Journal of Financial Economics, 37(1), 39–65. Bowerman, B. (2016). Business Statistics in Practice: Using Data, Modeling, and Analytics. McGraw-Hill Higher Education. Company, P., Jensen, C., & Meckling, H. (1976). Theory of the firm : managerial behavior , agency costs and ownership structure 1 . Introduction and summary In this paper WC draw on recent progress in the theory of ( 1 ) property rights , firm . In addition to tying together elements of the theory of e. 3, 305–360. Delinalie Chandra, Y. T. (2015). Pengaruh level diversifikasi, leverage, return on asset, umur perusahaan, dan sektor industri terhadap nilai perusahaan yang terdaftar di bei periode 2009–2011. Jurnal Akuntansi, 4(1). Harto, P. (2005). Kebijakan diversifikasi perusahaan dan pengaruhnya Terhadap kinerja: studi empiris pada Perusahaan publik di indonesia. Jensen, M. C., & Meckling, W. H. (1976). Theory of the firm: Managerial behavior, agency costs and ownership structure. Journal of Financial Economics, 3(4), 305–360. Kurniasari, S. E., & Tahun, E. T. (2014). Pengaruh Diversifikasi Usaha terhadap Kinerja Perusahaan yang Dimoderasi oleh Kepemilikan Manajerial. Universitas Dian Nuswantoro Jurnal, 1–9. Lucyanda, J., & Wardhani, R. H. K. (2017). Pengaruh diversifikasi dan karakteristik perusahaan terhadap kinerja perusahaan. Media Riset Akuntansi, 4(2), Hal-1. Salindeho, A. O., Saerang, I. S., & Maramis, J. B. (2018). Pengaruh Diversifikasi Usaha Terhadap Kinerja Keuangan Dan Return Saham Study Kasus Pada Perusahaan Manufaktur Automotive and Effect of Business Diversification of Financial Performance and Return Stock Case Stock in Automotive and Component Manufacturing. Jurnal EMBA, 6(3), 1078–1087. Setionoputri, A., Meiden, C., & Siagian, D. (2009). Pengaruh Diversifikasi Korporat Terhadap Excess value Perusahaan Manufaktur, Perdagangan Grosir dan Eceran, serta Properti dan Real Estat yang Terdaftar di BEI Tahun 2005-2007. Bidang Akuntansi Private: Akuntansi Keuangan Dan Pasar Modal (AKPM), 1–25. Spence, M. (2002). Signaling in retrospect and the informational structure of markets. American Economic Review, 92(3), 434–459. Sucipto, D. (2003). Penilaian Kinerja Keuangan. Jurnal Akuntansi: Universitas Sumatera Utara. Sumendap, R., Tommy, P., & Maramis, J. B. (2018). Analisis Perbandingan Kinerja Keuangan Berdasarkan Diversifikasi Segmen Bisnis Pada Industri Manufaktur Yang Go Public Comparative Analysis of Financial Performance Based on Diversification of Business Segments in Manufacturing Industry That Go Public. Jurnal Riset Akuntansi Dan Keuangan, 6(4), 2198–2207.